Application of the Role Playing Learning Model in Improving Verbal Communication Skills of Early Childhood at RA Al-Mustaqim in Air Meles Atas Village - Larasi Watia; Dewi Purnama; Aida Rahmi Nasution (Asian Journal of Applied Education (AJAE), 2023)
This study aims to apply the role playing learning model in improving verbal communication skills of early childhood at RA AL-Mustaqim in Air Meles Atas Village. Role playing is a learning tool that develops skills and understanding of human relations by living situations that are parallel to those that occur in real life. Sources of data used in this study are primary data and secondary data. Data collection techniques used are observation, interviews, and documentation. to analyze the data obtained is done with the principle of descriptive. Activities in data analysis in this study consisted of four interacting components, namely data collection, data reduction, data presentation and conclusion/verification. The results of the study showed that the role-playing learning model could improve the verbal communication skills of early childhood at RA Al-Mustaqim in Air Meles Atas Village.